Relationships between disease severity and measures of health status in people with interstitial lung disease in India: an observational study - Revati Amin; K. Vaishali; G. Arun Maiya; Aswini Kumar Mohapatra; Vishak Acharya; Marita T. Dale; Jennifer A. Alison (Scientific Reports)
Abstract The severity and progression of Interstitial Lung Disease (ILD) can vary due to environmental, cultural and genetic factors. The relationship between disease severity and factors that determine the health status of people with ILD living in lower middle-income countries like India has not been evaluated. This study aimed to determine whether there were relationships between disease severity with functional exercise capacity and Health Related Quality of Life (HRQoL) among people with ILD in India. This was a prospective, single center observational study. All participants performed Pulmonary Function Test (PFT) including Forced Vital Capacity (FVC) % predicted, Diffusing Capacity of the Lung for Carbon Monoxide (DLCO) % predicted, 6 min Walk Distance (6MWD), St. George’s Respiratory Questionnaire (SGRQ), modified Medical Research Council (mMRC) dyspnoea scale. Eighty participants with ILD were recruited from September 2020 and December 2022. There were strong correlations between 6MWD with DLCO % pred (Spearman rho 0.891) and between SGRQ Total score and DLCO % pred (Spearman rho 0.906). There were no correlations between 6MWD and FVC % pred (Spearman rho 0.206) or between SGRQ and FVC % pred (Spearman rho 0.113). This study demonstrated strong correlations between disease severity measured by DLCO % pred with both functional exercise capacity and HRQoL in people with ILD in India.